THE ROLE AND IMPORTANCE OF PHYSICAL EDUCATION AND MASS SPORTS TODAY (International journal of artificial intelligence, 2025)
This article covers the role of mass sports in society, its role in the formation of a healthy lifestyle and its importance in increasing the physical activity of the population. The state policy on the development of mass sports in the Republic of Uzbekistan, adopted laws and decisions, as well as existing infrastructure and activities are analyzed. The article also analyzes the state of development of mass sports on the basis of Statistics and presents suggestions and recommendations for topical problems and their elimination.